Drink consumption and traffic between university students: an integrative review (Research, Society and Development, 2020)
The alcohol is the main psychoactive drug used by university students, with a high prevalence of use, showing to the risk of damage to life. The aims of this study are to summarize publications on the prevalence of alcohol consumption among university students and to discuss their risk behavior in traffic. It is an integrative review, with studies published between 2010 and 2020 in the SciELO, MEDLINE and LILACS databases. After screening and applying the inclusion and selection criteria, 19 articles were selected. The analysis revealed that male students consume alcohol more frequently and women tend to increase this behavior. In addition, the exaggeration in alcohol consumption among students intensified during the college years. Although university students recognize the risk potential of the association of alcohol and traffic, there is evidence of dangerous attitudes in traffic demonstrating for non awareness of the dangers involved. Therefore, it is necessary to strengthen discussions and practical intervention in higher education institutions to consolidate the knowledge about the risks of drinking and driving and cause possible behavioral changes in order to reduce individual and collective damage.